Trabalho associado e solidário: sentidos, limites e possibilidades de mulheres empreendedoras no contexto do trabalho artesanal. - NASCIMENTO, Alany Barbosa (2021)
This dissertation aims to analyze the social relations of production in artisanal activity that emerge in the context of metamorphoses in the world of contemporary work, seeking to understand the construction of the meaning of this production in the daily lives of artisans. The study proposed here focuses on the process of social construction of collective and associated artisanal work spaces in the dynamics of urban life, organized by women living in precarious situations in the metropolitan region of São Luís / MA. Based on a case study of associate artisans, direct observation of activities and interviews at the São José de Ribamar Artisans Association and the Rio Grande Mother's Protection Association of Santo Antônio in São Luís. position of artisans in these associated work spaces would enable experiences of autonomy and recognition of social and economic ties.